Emotional Well-Being and Cognitive Function Have Robust Relationship With Physical Frailty in Institutionalized Older Women - Furtado, Guilherme Eustáquio; Caldo, Adriana; Vieira-Pedrosa, Ana; Letieri, Rubens Vinícius; Hogervorst, Eef; Teixeira, Ana Maria; Ferreira, José Pedro (Frontiers in Psychology, 2020)
Introduction: Frailty associated to core dimensions of psychological well-being (PwB) has appeared as a possible new frailty phenotype named Psychological Frailty, implying a parallel to physical frailty (PF). Very little is known about the associations between mental well-being, specially, emotional, mood and self-perception dimensions, and the frailty syndrome in institutionalized older populations. The present study aims to examine the interlink between PF phenotype and core dimensions of PwB in Portuguese institutionalized-dwelling older women. Methods: Cross-sectional data were collected. A total of 358 older women aged 75 years or more, were recruited from four nursing homes within the city of Coimbra, and asked to complete a sociodemographic and a general health assessment survey. The main PwB dimensions were assessed in all participants: i) Global cognitive status was assessed using The Montreal Cognitive Assessment neuropsychology test; ii) Self-perception was screened using the General self-efficacy scale and Global self-esteem scale; iii) CES-D of depression, and Perceived stress scale were used to screen mood states; iv) Subjective happiness, Satisfaction with life and Attitudes to aging psychometric rating scales were used to screen for emotional well-being. The syndrome of PF was assessed using the Fried of PF phenotype, that includes Weight Loss, Weakness, Slowness, Exhaustion, Low Physical Activity levels assessments. Results: Frail older women had a poor score in all PwB outcomes, except for global self-esteem and satisfaction with life. A hierarchical regression model analysis showed that global cognitive status and emotional well-being of subjective happiness and attitude to ageing showed a significant negative relationship with PF in both unadjusted and adjusted models (explaining 34% and 40% of variance, respectively). Conclusion: Emotional well-being and Global cognitive performance are strongly associated with PF. Implementing active lifestyle interventions to improve positive psychological outcomes using geriatric assessments could assist in the older institutionalized patient’s physical and mental health care.